Drivers of Cyanobacterial Blooms in a Hypertrophic Lagoon - Bartoli, Marco; Zilius, Mindaugas; Bresciani, Mariano; Vaiciute, Diana; Vybernaite-Lubiene, Irma; Petkuviene, Jolita; Giordani, Gianmarco; Daunys, Darius; Ruginis, Tomas; Benelli, Sara; Giardino, Claudia; Bukaveckas, Paul A.; et al. (Frontiers in Marine Science, 2018)
The Curonian Lagoon is Europe’s largest lagoon and one of the most seriously impacted by harmful blooms of cyanobacteria. Intensive studies over the past 20 years have allowed us to identify the major drivers determining the composition and spatial extent of hyperblooms in this system. We summarize and discuss the main outcomes of these studies and provide an updated, conceptual scheme of the multiple interactions between climatic and hydrologic factors, and their influence on internal and external processes that promote cyanobacterial blooms. Retrospective analysis of remote sensed images demonstrated the variability of blooms in terms of timing, extension and intensity, suggesting that they occur only under specific circumstances. Monthly analysis of nutrient loads and stoichiometry from the principal tributary (Nemunas River) revealed large interannual differences in the delivery of key elements, but summer months were always characterized by a strong N (and Si) limitation, that depresses diatoms and favors the dominance of cyanobacteria. Cyanobacteria blooms result in transient (night-time) hypoxia, which stimulates the release of iron-bound P, producing a positive feedback for blooms of N-fixing cyanobacteria. Other biotic factors, such as dreissenid mussels, chironomid larvae, cyprinids and large bird colonies, may also promote P recycling during summer, but their role as drivers of cyanobacteria blooms is understudied.